(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
We analyze the collection of poems titled Los heraldos negros by César Vallejo, with the object of determining the fundamental isotopies which articulate the vision of the world expressed in these poems. From the isotopy we have named “tragic conscience”, the poetic text generates three new thematic isotopies (God, childhood, woman) which appear as a response to the absurd perception of life. For this analysis we use contextual references taken from the author’s biography and the historic period in which Vallejo lived, particularly the references of Existential philosophy and Marxist philosophy. We also base this analysis on the notions of man-Adam and man-Christ as expressions of the personal vision which is manifested in Vallejo’s poetic idiolect.